Mild and Asymptomatic Coronavirus Disease in Children, Adolescents, and Household Contacts and Prolonged Viral Excretion - Machado, Márcia Borges; Fajardo, Thamirys Cosmo Grillo; de Oliveira, Lourival Benedito; Quadros Junior, Antonio Carlos de; Catalan, Daniel Thome; Piovesan, Karim Cristina; Garcia, Maria Emília De Domenico; da Silva, Maurício Feliciano; Dezena, Rita de Cássia de Aguirre Bernardes; Passos, Saulo Duarte (International Journal of Microbiology, 2022)
Problem. The clinical presentation of coronavirus disease (COVID-19) in children remains controversial. This study analyzed viral excretion in children and adolescents with mild-to-moderate disease and their household contacts, who were treated in Jundiaí, Brazil between March and November 2020, before vaccination was available. Method. This was a prospective, observational, and descriptive cohort study. Nasopharyngeal swabs and blood were collected six times at weekly intervals. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) tests and immunoglobulin (Ig) G and IgA assays were used to test for COVID-19. Results. Overall, 419 children and 253 adults were enrolled. There was a significant correlation between qRT-PCR confirmation and the 1 to <5 years age group (p=0.038). Serology changes or recent infections were detected significantly in children <6 months (IgG, p=0.006; IgA, p=0.001) and >5 years of age (IgA, p=0.040; IgG, p=0.031). The mean and median time-to-positivity (using qRT-PCR) was 17 days, with a minimum of 6 and a maximum of 34. Among adults, the mean and median time-to-positivity was 12.6 and 9 days, respectively, with a minimum of 6 and a maximum of 45. Conclusion. Oligosymptomatic conditions may delay diagnosis and facilitate viral transmission. Pediatric-focused research is required, and specific protective measures for children <6 months of age should be considered.